Combination of Essential Oils of Ylang-Ylang (Cananga Odorata), Jasmine (Jasminum Sambac), and Mint Leaves (Mentha Piperita) TestingAphrodisiac on Male Mice Formulated in Candle Forms - Tio Widia A. marpaung; Kintoko; Wahyu Widyaningsih; Moch Saiful Bachri; Amelia Regina Arsyad (Jurnal FARMASIMED (JFM), 2025)
This study explored the potential of Jasminum sambac (jasmine) and Mentha piperita (peppermint) as natural sexual stimulants (aphrodisiacs) to enhance sexual activity in males and females through the use of essential oils. The main objective was to identify the most effective combination of essential oil formulations, which were evaluated through several biological and physiological parameters, including sexual behavior in mice, sperm quality, testicular histopathology, and wax-based formulations as the delivery medium. Three formulations were tested: P1 (3:1:1), P2 (1:3:1), and P3 (1:1:3), administered to mice using a humidifier via inhalation. Sexual behavior was assessed through mounting latency and mounting frequency as indicators of libido. Sperm quality parameters included morphology, motility, viability, and sperm count. Testicular histopathology was examined to evaluate tissue structure and spermatogenesis activity. The results demonstrated that the P1 formulation was the most effective, showing the highest aphrodisiac activity. In the sexual behavior test, P1 recorded an activity value of 21±6.2, indicating enhanced libido. Sperm quality testing also confirmed the superiority of P1, with the lowest sperm abnormalities (5.3±1.53), highest motility (82±7.5), highest viability (85.6±4.58), and the greatest sperm count (53,300±16,653.3). Although testicular histopathology revealed a slight reduction in spermatogenic cells across all treatment groups, the change was not significant in the P1 group compared to the control. Overall, the P1 formulation improved libido and sperm quality more effectively than P3 and the control group, indicating its potential to be developed as an aphrodisiac preparation based on natural essential oils.